The Immobilization of Fructose Dehydrogenase on Nanoporous Gold Electrodes for the Detection of Fructose. Issue 4 (16th February 2017) - Siepenkoetter, Till; Salaj‐Kosla, Urszula; Magner, Edmond
Abstract: Nanoporous gold electrodes were utilized as a support for the detection ofd ‐fructose. The immobilization of fructose dehydrogenase was achieved by adsorption on thiol‐ and diazonium‐bound carboxylic acid functional groups and subsequent crosslinking through cabodiimide‐initiated amide bond formation. The biosensor showed a linear response in the range 0.05–0.3 mM ofd ‐fructose with a sensitivity of 3.7±0.2 μA cm −2 mM −1 and a limit of detection of 1.2 μM. The response of the biosensor in a range of natural sweeteners and beverages compared very favorably to the results obtained by a commercially available kit. Accurate readings were obtainable after a very fast response time of less than 5 seconds. The biosensor showed high specificity towardsd ‐fructose in the presence of interfering sugars. Abstract : Sweet sensation : Nanoporous gold electrodes with pore sizes ranging from 4 to 62 nm are prepared and utilized for the immobilization of fructose dehydrogenase as ad ‐fructose biosensor. The response of the biosensor compares favorably with a commercially available enzyme kit when tested on a range of natural sweeteners and beverages.